Induced Negative Mood Increases Dictator Game Giving - Pérez-Dueñas, Carolina; Rivas, M. Fernanda; Oyediran, Olusegun A.; García-Torres, Francisco (Frontiers in Psychology, 2018)
The study examines the influence of induced negative mood on dictator game giving with two recipients. Participants (N = 63) played the role of a dictator in a three-player dictator game. They could choose among two options: an altruistic option, where two receivers receive 10 Euros and the dictator himself receives nothing, or a selfish option, where the dictator himself receives 5 Euros and both receivers receive nothing. For half of the participants, the second option entailed that only one receiver receives nothing and the other receives 10 Euros. After four rounds, participants were randomly assigned to look at ten pictures with either positive or negative emotional content with the purpose of inducing positive or negative mood. The results show that looking at pictures with negative emotional content increases anxiety and skin conductance and increases dictator game giving in the remaining four rounds of the game. On the other hand, whether the selfish option would imply that one or both recipients receive nothing does not seem to have a strong influence on dictator game giving.